A study on the outreach programs of selected private academic libraries in Metro Manila - Casimiro, Noel Salvador B.; Lapuz, Elvira B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2012)
Since librarianship is a profession based on service, it is crucial to identify and describe activities that promote and put into action the notion of service. An example of this activity is library outreach where librarians are conducting information and other services outside the confines of their library. This study concentrated on the outreach programs of six selected private academic libraries in Metro Manila namely: Ateneo de Manila University Rizal Library, Far Eastern University Library, Lyceum of the Philippines University Sotero H. Laurel Academic Resources Center, University of the East-Manila Library, The University of Manila Library, and the University of Santo Tomas Miguel de Benavides Library.
The library directors or librarians-in-charge of outreach of the six selected libraries were surveyed and interviewed. Items in the survey questionnaire were mainly based from the questionnaire of the Systems and Procedures Exchange Center (SPEC) kit of the Association of Research Libraries (ARL) titled "The Role of ARL Libraries in Extension/Outreach" and partly based from the questionnaire of Dalisay (1995) in her MLIS thesis entitled "Public Relations Programs in Academic Libraries in Metro Manila". The questionnaire determined the outreach programs' background, types of services, methods and approaches, contributions of individual librarians, and impact.
The main findings of this study show that: (a) outreach programs are institutionalized in all the respondent libraries and these programs vary in terms of activities implemented; (b) the university's mission propel the libraries to conduct outreach; (c) various people in the university and library are involved in the planning and implementation of library outreach programs; (d) the most common type of outreach program in the six academic libraries is community service; (e) the most common method of promoting outreach programs is the use of correspondence; (f) reference and information services are usually free for people not affiliated with the university and library; (g) all six private academic libraries have librarians provide services to professional organizations and participate in these organizations of various subject fields; (h) only one among the six respondent libraries does not consider outreach as a basis for promotion and tenure of librarians; (i) majority of the respondent libraries experienced an increase in revenues and gifts as a result of outreach; (j) university outreach service is the most common benchmark for outreach program success among the six libraries; (k) mostly benefits are perceived by librarians when conducting outreach such as the broadening of librarians and library staff's perspectives; (1) strain on limited resources and unreasonable expectations and/or demands of users are the common issues and concerns in outreach programs; and (m) the thought and feeling of sharing and giving happiness to less fortunate people make the libraries continue on doing outreach.
Recommendations of the researcher include: (a) all outreach programs should be part of the libraries' regular services and programs; (b) librarians who are interested in outreach should consult with fellow librarians who have the experience; and (c) outreach programs of other types of libraries must also be studied.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Library outreach programs -- Philippines -- Manila Metropolitan Area; Academic libraries -- Philippines -- Manila Metropolitan Area